Pregnancies in women receiving renal transplant for lupus nephritis: description of nine pregnancies and review of the literature. (October 2015) - Campise, M; Giglio, E; Trespidi, L; Messa, P; Moroni, G
Background: Few data are available on pregnancy in renal transplanted women for lupus nephritis (LN). Methods: Among 38 women with LN who received a renal transplant in our Unit, three had nine pregnancies. During the pregnancies, patients were followed by a multidisciplinary team including gynecologists and nephrologists. Results: Two patients received a living related and one a deceased kidney transplant. The immunosuppressive therapy consisted of steroids calcinurin inhibithors and mycophenolate mofetil. The last drug was substituted with azathioprine in prevision of pregnancy. All patients had normal renal function and urinalysis. In two patients some signs of immunological activity persisted after transplantation. Five pregnancies ended in miscarriage and four in live births. Two pregnancies were uneventful. Pre-eclampsia occurred in a hypertensive patient in two pregnancies that ended in preterm delivery in one case and in a small for gestation age in both cases. And finally, follow-up graft function and urinalysis continued to be normal in all patients. Conclusions: After renal transplantation our LN women continue to have frequent miscarriages. The other pregnancies ended in live births and, with the exception of pre-eclampsia in a hypertensive patient, no renal or extra-renal complications occurred during or after pregnancy, even in cases with active immunological tests.